Big Book of Stars and Planets (Big Books) - Emily Bone (London Usborne Publishing Ltd., 2016)
Children can explore the wonders of space in this incredible picture book with giant fold-out pages full of fascinating facts to satisfy the curiosity of every young space enthusiast. From the Sun and the planets in our Solar System to massive stars and vast galaxies and lots, lots more, there's a whole universe to discover.